Does qard financing fortify the trust of bank customers? Lessons from Islamic regional banks in Indonesia - Widarjono, Agus; Hendri, Zul; Shuib, Mohd Sollehudin; Jaya, Yozar Putra (Review of Islamic Social Finance and Entrepreneurship, 2026)
Purpose – This study investigates the impact of Qard financing on customer trust in Islamic banks in Indonesia using a nonlinear approach.Methodology – We examine 123 Islamic regional banks (IRBs) from 2016 to 2023 using quarterly data. The estimation method is the dynamic panel regression method using the generalized methods of moments (GMM). The trust of IRBs’ customers is proxied by third-party funds (TPF).Findings – Moderate Qard financing strengthens customer confidence; however, as it exceeds the optimal level, the effect of Qard financing on TPF becomes negative. More importantly, the results indicate that the positive impact of Qard financing on customer confidence weakens as banks face high liquidity risk. Implications – First, Qard financing must be conducted in a measurable and optimal manner to avoid risk perceptions that are likely to weaken fund collections. Second, IRBs need to warrant that the expansion of Qard financing is balanced with prudent liquidity management. The Indonesian Financial Services Authority (OJK) likely includes Qard financing as one of the IRB performance indicators.Originality – Our study is a pioneer in investigating the role of social financing in customer trust using a non-linear approach.